Anti-Neuronal IgG4 Autoimmune Diseases and IgG4-Related Diseases May Not Be Part of the Same Spectrum: A Comparative Study - Endmayr, Verena; Tunc, Cansu; Ergin, Lara; De Rosa, Anna; Weng, Rosa; Wagner, Lukas; Yu, Thin-Yau; Fichtenbaum, Andreas; Perkmann, Thomas; Haslacher, Helmuth; Kozakowski, Nicolas; Schwaiger, Carmen; et al. (Frontiers in Immunology, 2022)
Background IgG4 is associated with two emerging groups of rare diseases: 1) IgG4 autoimmune diseases (IgG4-AID) and 2) IgG4-related diseases (IgG4-RLD). Anti-neuronal IgG4-AID include MuSK myasthenia gravis, LGI1- and Caspr2-encephalitis and autoimmune nodo-/paranodopathies (CNTN1/Caspr1 or NF155 antibodies). IgG4-RLD is a multiorgan disease hallmarked by tissue-destructive fibrotic lesions with lymphocyte and IgG4 plasma cell infiltrates and increased serum IgG4 concentrations. It is unclear whether IgG4-AID and IgG4-RLD share relevant clinical and immunopathological features. Methods We collected and analyzed clinical, serological, and histopathological data in 50 patients with anti-neuronal IgG4-AID and 19 patients with IgG4-RLD. Results A significantly higher proportion of IgG4-RLD patients had serum IgG4 elevation when compared to IgG4-AID patients (52.63% vs. 16%, p = .004). Moreover, those IgG4-AID patients with elevated IgG4 did not meet the diagnostic criteria of IgG4-RLD, and their autoantibody titers did not correlate with their serum IgG4 concentrations. In addition, patients with IgG4-RLD were negative for anti-neuronal/neuromuscular autoantibodies and among these patients, men showed a significantly higher propensity for IgG4 elevation, when compared to women (p = .005). Last, a kidney biopsy from a patient with autoimmune paranodopathy due to CNTN1/Caspr1-complex IgG4 autoantibodies and concomitant nephrotic syndrome did not show fibrosis or IgG4+ plasma cells, which are diagnostic hallmarks of IgG4-RLD. Conclusion Our observations suggest that anti-neuronal IgG4-AID and IgG4-RLD are most likely distinct disease entities.